PHACOMORPHIC GLAUCOMA WITH SENILE IMMATURE CATARACT: A CASE REPORT - Widianty, Ruth Syeela (Syntax Corporation Indonesia, 2025)
Phacomorphic glaucoma is a secondary angle-closure glaucoma caused by lens thickening due to cataract formation process, potentially leading to increased intraocular pressure and a risk of permanent optic nerve damage, resulting in visual impairment. This report discusses a case involving a 57-year-old female presenting with blurred vision and pain in one eye, diagnosed with phacomorphic glaucoma with senile immature cataract based on history taking, and ophthalmological examination. The findings revealed decreased visual acuity, lens opacity in the left eye with a positive shadow test, increased iop, and shallow anterior chamber. the patient initially received medical therapy to lower intraocular pressure, followed by definitive treatment, which consisted of a combination of phacoemulsification with intraocular lens implantation and trabeculectomy. postoperative results showed symptom and visual acuity improvement, although the prognosis for visual function depends on the degree of optic nerve damage prior to treatment. primary management of phacomorphic glaucoma involves cataract extraction, which causes pupil block, that is often combined with trabeculectomy to effectively control intraocular pressure.